The Effects of Non-Guided Versus Guided Podcast Production on Perception of English Reading Skills in Undergraduate Nursing Students: A Quasi-Experimental Study. - Phuwayanon, Sirinthip; Namprom, Nethong; Woragidpoonpol, Patcharee; Daroonratsamee, Suwimol; Bressington, Daniel Thomas (Nursing Reports, 2025)
Background: Nurses need strong English language skills to access knowledge and promote evidence-based practice. Podcast production is a promising pedagogical strategy to improve language skills. However, the effects of podcast production on nursing students' perceived English reading proficiency and the most effective production instructional approaches remain unreported. Aim: To examine the impacts of podcast production on undergraduate nursing students' perceptions of English reading skills and compare the effectiveness of two podcast production teaching methods. Design: A quasi-experimental study. Methods: 78 third-year nursing students in Northern Thailand were divided into an experimental group (n = 39) and a control group (n = 39). The experimental group received specific guidelines for podcast production, while the control group used a non-guided method. Outcomes included students' perceptions of their English reading skills and the experimental group's attitudes toward podcast production guidelines. Results: Pre-test scores for perceived English reading skills were similar between groups (t = −1.029, p = 0.307). ANCOVA revealed that after controlling for pre-test scores, the control group reported significantly higher adjusted post-test scores than the experimental group (F = 5.001, p = 0.028). Students in the experimental group expressed positive attitudes toward the podcast production guidelines. Conclusions: Both podcast production approaches were effective; however, the less-guided approach showed greater improvement in students' perceptions of their English reading skills. This approach may encourage student autonomy, creativity and deeper engagement. Podcast production emerges as a valuable student-centred learning strategy to improve perceptions of language skills, but finding a balance between support and independence during instruction seems important to maximise its potential benefits.